Mis-Allocation within Firms: Internal Finance and International Trade - Sebastian Doerr; Dalia Marin; Davide Suverato; Thierry Verdier; Thierry Verdier (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper develops a novel theory of capital mis-allocation within firms that stems from managers' empire building and informational frictions within the organization. Introducing an internal capital market into a two-factor model of multi-segment firms, we show that international competition imposes discipline on managers and reduces capital mis-allocation across divisions, thereby lowering the conglomerate discount. The theory can explain why exporters exhibit a lower conglomerate discount than non-exporters (a new fact we establish). Testing the model's predictions with data on US companies, results suggest that Chinese import competition significantly reduces managers' over-reporting of costs and improves the allocation of capital within firms.
Keywords: F12; G30; L22; D23; 330; multi-product firms; trade and organization; internal capital markets; conglomerate discount; China shock